Likuditas Dan Efisiensi Operasional Bank: Bagaimana Peran Moderasi Ukuran BankPerusahaan - Bowi, Devi Mareta; Rita, Maria Rio (AFRE (Accounting and Financial Review), 2020)
This study empirically examines the effect of liquidity on the efficiency of banking operations in Indonesia, with moderation in company size. To measure the level of operational efficiency, the BOPO ratio is used, which is the ratio of operating costs to operating income and liquidity is proxied by the LDR (Loan to Deposit Ratio) ratio. The sample in this study were 35 state-owned (private) and private (BUSN) banks that listed and published complete financial statements on the Indonesia Stock Exchange for the period of 2016 - 2018. This study proves that LDR has a significant negative effect on (BOPO) and the size of the company moderates / weaken the influence of LDR on BOPO. The greater the size of the bank, the effect of the LDR on operational efficiency will be weaker.Â DOI: https://doi.org/10.26905/afr.v3i1.4093